Implementasi Website Profil Sebagai Strategi Peningkatan Penjualan Di Toko Kue Macaron Tuffero - Rudy Ariyanto; Rakhmat Arianto; Imam Fahrur Rozi; Erfan Rohadi; Farida Ulfa; Ahmadi Yuli Ananta (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity was carried out with the aim of enhancing the competitiveness and brand image of Macaron Tuffero through the development of a Profile Website as an effective and sustainable digital promotion medium. The partner of this program is the Macaron Tuffero SME, which operates in the production of cakes and desserts, located in Dau District, Malang Regency. The activity involved the business owner and staff as primary participants who collaborated actively with the community service team from Politeknik Negeri Malang. The main problem faced by the partner was the limited use of digital promotion media and the absence of an official platform to professionally present the business profile. To address this issue, the activity was implemented through five main stages: needs analysis, website design and architecture planning, system development and implementation, testing, and website usage training. The website was developed using the WordPress platform with the WooCommerce plugin to facilitate product catalogs and online ordering features. The results show that the developed website functions properly, consistently presents the business’s visual identity, and integrates with various social media and marketplace platforms. The website also provides convenience for the business owner to independently update content. Overall, this community service program successfully delivered a practical digital solution that contributes to marketing capacity enhancement and supports digital transformation among SMEs in the technology-based economy era.